AB0605 Procalcitonin might be used for discriminating infections from increased disease activity in primary sjÖgren syndrome. (12th June 2018) - Arican Tarim, B.; Tezcan, M.E.; Orcun, A.; Keskin, O.
Abstract : Background: Procalcitonin is a polypeptide which is secreted as a response to bacterial stimulus and accepted as an early and sensitive marker of infection. In healthy subjects procalcitonin should be <0.1 ng/mL. In case of infection it may rises over 0.5 ng/mL[. 1 Its level in inflammatory diseases usually does not reach to such high levels as in infections. Differentiating infection and disease activation may be confusing in autoimmune diseases. For this purpose, there were several studies that evaluated the role of procalcitonin for excluding infection on suspicion of increased autoimmune disease activity. 2 Objectives: As far as we know, there is no study in literature that evaluated procalcitonin levels in patients with primary Sjögren's syndrome (pSS). Our aim is to evaluate procalcitonin levels in pSS and determine whether we can use it as a marker to differentiate infection from disease activation. Methods: The following two groups of patients were included in the study: Forty-eight patients with pSS, who met ACR 2012 Classification Criteria for Sjögren's Syndrome; and fifty-three subjects as control group who have no chronic diseases. Patients with possible infection were excluded according to their clinical evaluation and laboratory data. Then, serum procalcitonin levels were compared between the groups. Finally, we evaluated the correlation between disease activity, measured by Sjögren's syndrome disease activity index (SSDAI) and procalcitonin levels. Results: Procalcitonin levels in pSS group were found statistically higher than control group, whereas it was still in normal ranges (p<0, 01). Furthermore, no correlation was found between disease activation and the procalcitonin levels (p=0.63). Conclusions: Procalcitonin levels were found higher in pSS patients. But, none of the patients had clinically significant increase in procalcitonin. We thought that with careful clinical evaluation, procalcitonin would be an indicator for differentiating infection from disease activation in pSS patients. References: [1] Oczenski W, Fitzgerald RD, Schwarz S (1998) Procalcitonin: a new parameter for the diagnosis of bacterial infection in the peri-operative period. Eur J Anaesthesiol15: 202–9. [2] Korczowski B, Kowalczyk JR, Bijak M, Rusin J (2003) Concentration of procalcitonin and C-reactive protein in serum and erythrocyte sedimentation rate in active autoimmune diseases in children. Pol Merkur Lekarski. Aug;15(86):155–7. Disclosure of Interest: None declared